Susceptibility of Campylobacter jejuni to organic acids and monoacylglycerols - Molatová, Z; Skrivanová, E; Macias, B; McEwan, N R; Brezina, P; Marounek, M (Folia microbiologica, 2010)
Organic acids can be used as feed supplements or for treatment of poultry carcasses in processing plants. The antimicrobial activity of nineteen organic acids and two monoacylglycerols in cultures of Campylobacter jejuni CCM 6214(T) (ATCC 33560) was determined using a SYBR Green-based real-time PCR assay. The IC(50) was a concentration at which only 50 % of a bacteria specific DNA sequence was amplified. Caprylic, capric and lauric acids were the most efficient antimicrobials among the compounds tested (IC(50) < or = 0.1 mg/mL). In a weakly acidic environment (pH 5.5), the antimicrobial activity was more pronounced than at pH 6.5. At pH 5.5, oleic and fumaric acid also had clear antimicrobial activity, as did monocaprylin. The antimicrobial activity of acetic, butyric, stearic and succinic acid was low. In cells treated with fumaric acid, the potential of potassium and tetraphenylphosphonium ion-selective electrodes changed, indicating an increase in cytoplasmic and outer membrane permeability, respectively. No changes in membrane permeability were observed in cells treated with capric acid or monocaprin. Transmission electron microscopy revealed separation of the inner and outer membrane in cells treated with capric and fumaric acid, as well as cytoplasmic disorganization in cells exposed to capric acid.
Keywords: barvení a značení; chinoliny; Microscopy, Electron, Transmission; Microbial Sensitivity Tests; Cell Membrane Permeability; Cell Membrane; kyseliny karboxylové; organické látky; Campylobacter jejuni; benzothiazoly; mikrobiální testy citlivosti; Quinolines; počet mikrobiálních kolonií; Inhibitory Concentration 50; Diamines; Anti-Bacterial Agents; diaminy; inhibiční koncentrace 50; transmisní elektronová mikroskopie; monoglyceridy; permeabilita buněčné membrány; Staining and Labeling; polymerázová řetězová reakce; Colony Count, Microbial; Monoglycerides; Polymerase Chain Reaction; Organic Chemicals; Carboxylic Acids; Benzothiazoles; buněčná membrána; antibakteriální látky